UPAYA MENINGKATAN PERKEMBANGAN KOGNITIF DENGAN MEMBILANG MELALUI MEDIA PERMAINAN CONGKLAK PADA ANAK KELOMPOK B DI PAUD PUTRA PERTIWI KECAMATAN LUBUK SANDI KABUPATEN SELUMA - Deni Yopita Sari; Rika Partikasari; Mimpira Haryono (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The purpose of this study was to determine children's cognitive development through the congklak game method in PAUD Pitra Pertiwi, Lubuk Sandi District, Seluma Regency. This classroom action research uses the Jhon Elliot model, where each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The results of the research obtained show that the application of playing congklak can improve the cognitive development of children aged 5-6 years in PAUD Putra Pertiwi, Lubuk Sandi District, Seluma Regency. This increase occurs because, at each stage of the meeting, improvements are made, so that children get used to learning activities using congklak media. The cognitive development of children by counting through congklak media in PAUD Putra Pertiwi Seluma Regency reaches 96% with the criteria developing according to expectations (BSH).